Intravoxel Incoherent Motion in Normal Pituitary Gland: Initial Study with Turbo Spin-Echo Diffusion-Weighted Imaging - Kamimura, K. (AJNR Am J Neuroradiol, 2016)
BACKGROUND AND PURPOSE: DWI with conventional single-shot EPI of the pituitary gland is hampered by strong susceptibility artifacts. Our purpose was to evaluate the feasibility of intravoxel incoherent motion assessment by using DWI based on TSE of the normal anterior pituitary lobe. MATERIALS AND METHODS: The intravoxel incoherent motion parameters, including the true diffusion coefficient (D), the perfusion fraction (f), and the pseudo-diffusion coefficient (D*), were obtained with TSE-DWI in 5 brain regions (the pons, the WM and GM of the vermis, and the genu and splenium of the corpus callosum) in 8 healthy volunteers, and their agreement with those obtained with EPI-DWI was evaluated by using the intraclass correlation coefficient. The 3 intravoxel incoherent motion parameters in the anterior pituitary lobe were compared with those in the brain regions by using the Dunnett test. RESULTS: The agreement between TSE-DWI and EPI-DWI was moderate (intraclass correlation coefficient = 0.571) for D, substantial (0.699) for f', but fair (0.405) for D*. D in the anterior pituitary lobe was significantly higher than in the 5 brain regions (P < .001). The f in the anterior pituitary lobe was significantly higher than in the 5 brain regions (P < .001), except for the vermian GM. The pituitary D* was not significantly different from that in the 5 brain regions. CONCLUSIONS: Our results demonstrated the feasibility of intravoxel incoherent motion assessment of the normal anterior pituitary lobe by using TSE-DWI. High D and f values in the anterior pituitary lobe were thought to reflect its microstructural and perfusion characteristics.